ALASAN PAKISTAN MENUNDA PEMBERIAN STATUS MOST-FAVORED NATION KEPADA INDIA TAHUN 2011-2014 - Wulandari Endah Susilowati (HI 16 UMY 176, 2015)
The relation between two neighborhood countries, Pakistan and India, has not been really good since before the independence of the two countries. They were one country at first and became a rival due to the differences of belief. The relationship of both countries was not really smooth, there were some conflicts and it caused wars between the two countries. In 2008, the relation has become worse due to the terrorism act in Mumbai, India. The suspect of the act was Lashkar-e-Thaiba that is based in Pakistan and the perpetrators were Pakistani citizens. In 2011, Pakistan said they would grant Most-Favored Nation (MFN) status to India in 2012 that has not been granted since they joined World Trade Organization (WTO) in 1995 to cool down the tension between the two countries, but later Pakistan chose to postpone the granting until now.